Symptomatic first urinary tract infection in children and underlying kidney and urinary ttract abnormalities from a tertiary care hospital in India - Dey, PK; Banerjee, J; Singh, RP; Pan, A; Chatterjee, A (Journal of College of Medical Sciences-Nepal, 2014)
Objective The aim of this study was to describe the characteristics and the clinical evolution of first documented symptomatic Urinary Tract Infection and to detect underlying abnormalities of the kidney and urinary tract if any. Methods Prospective observational study on 102 patients (6 months to 5 yrs) with first documented symptomatic Urinary Tract Infection diagnosed by positive urine culture in the department of Paediatrics, G.S.V.M Medical College, Kanpur, India between January 2008 and June 2009. Antibiotics were given according to the sensitivity pattern. All children were evaluated with renal bladder ultrasonogram and voiding cystourethrography. Results Out of 102 patients 62 (60.78%) girls and 40 (39.21%) boys, most of the patients (62.7%) within 6 months to 2 years old. The commonest presentation was fever (84.3%).The commonest organism was E.Coli (80.37%). Overall most common underlying abnormality was VUR, found in 31(30.31%) children. Other abnormalities were urolithiasis(4.9%), ureteropelvic junction obstruction (3.92%),Mild hydronephrosis (2.9%), ureteric duplex(0.98%), posterior urethral valve(0.98%), renal duplex (0.98%). Conclusion In our study 45.09% children had underlying abnormalities which may be a potential risk factor for urinary tract infection. Better recognition of risk factors, prompt diagnosis and early intervention are sufficient enough to maintain normal renal function and healthy lifestyle. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-3, 45-53 DOI: http://dx.doi.org/10.3126/jcmsn.v9i3.10222